(3GdOQQ GdaGNQI aj cTa CSQGQ GdNdGUI GdRGgQIs - (3LeGd GdOjf CHh eMeO Ydj Hf YHO Gddg Hf CMeO Hf CHi GdNjQs; (3CHh GdMSf CMeO Hf GdMSjf Hf eMeO Hf CHj HcQ GdQUGU GdUfYGfjs ((3YKeGf Hf Ydi Hf eMeO GdeDPf s)
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdefGf GdYXje GdTCf s
(3BNQgG (B:s
(3hGdeSDhd GdOYGA ef cGaI GdENhGf bGd UGMH GdcJGH (B: (3hcGf GdaQGZ ef JCdjag SfI SHYjf hSHYeGFI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG JUMjMGJ hebGHdGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ GdZQHjI (B((3Yde GdcdGe (B84) s
Keywords: (3GdJhMjO hGdedd hGdfMds